The Development of Chemical E-Module Based on Problem of Learning to Improve The Concept of Student Understanding - U.Z., L.M. Zulfahrin; Haryono, Haryono; Wardani, Sri (Innovative Journal of Curriculum and Educational Technology, 2019)
Teaching materials are a set of learning facilities or tools that contain learning materials, methods, boundaries, and how to evaluate a systematic and attractive designed to achieve the expected goal, namely achieving competence or sub competence with all its complexity. This research aims to (1) analyzing the chemical materials used in the class of XI IPA, (2) to develop the teaching materials that should be used in chemical learning, (3) test the feasibility of e-module based on problem chemical, (4) to examine the effectiveness of the chemical e-module based on problem based learning. This research uses the model of Research and Development (R & D). The teaching materials used in chemistry learning in the classes of XI IPA are LKS and published books. The teaching materials are developed in the form of e-module of chemical based on problem-based learning. The steps include: Presenting the problem, organizing the students, investigation of the group, Development, and presentation of the work, and evaluation of the results of the investigation. The feasibility of an e-module based on the problem of chemical media experts and the materials and practitioner’s validation. The validation is done in two stages. On the feasibility Validation e-module chemical based on problem-based learning in steps two, the result obtained e-modules based on the problem of chemistry that has achieved maximum score with the category is good that can be used in learning. Based on the effectiveness test that is using descriptive test, prerequisite test, and hypothesis test, it can be concluded that e-module of chemical based on problem-based learning can improve the concept of student understanding. The results of the study are expected to strengthen the theory of learning technology, especially on the development of chemical teaching materials. This Research as a means of procurement of educational products, i.e., e-module based on the problem-based learning that is flexible, efficient and effective, and can be used as a source of reading capable of providing an understanding of the enhanced student concepts mastery in learning of chemistry.